The participation of singlet oxygen in a photocitotoxicity of extract from amazon plant to cancer cells - Tcibulnikova, Anna V.; Degterev, Igor A.; Bryukhanov, Valery V.; Roberto, Mantuanelly M. [UNESP]; Campos Pereira, F. D. [UNESP]; Marin-Morales, M. A. [UNESP]; Slezhkin, Vasily A.; Samusev, Ilya G. (SPIE, the international society for optics and photonics, 2017)
We have been searching for new photosensitizers (PS) for photodynamic therapy (PDT) of cancer based on extracts from Amazonian plants since 2009. In this paper, we demonstrate that, under certain conditions, the extract from fruits of the Amazonian palm Euterpe oleraceae (popular name Açaí) can serve as a PS for PDT treatment of murine breast cancer cells (4T1 cell line). We have been first to show directly that the photodynamic effect of plant PS is due to singlet oxygen.
Keywords: amazon Palm Tree; cancer cells; laser; MTT method; nanoemulsion; PDT; plant extract; PS; singlet oxygen; UV-Vis and fluorescent spectra